Strategi Konservasi di Pulau Sulawesi dengan Menggunakan Tarsius sebagai Flagship Spesies - Shekelle, Myron; Leksono, Suroso Mukti (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2004)
We present a strategy to preserve the biodiversity of Sulawesi and nearby islands chains. Sulawesi is the primary landmass in the biogeographic zone known as Wallacea, and is listed as one of the worldâ€™s top 25 hotspots at threat for major loss of biodiversity. Sulawesi is hypothesized to be subdivided into regions of endemism. We argue that the best strategy for preserving the totality of Sulawesi biodiversity, given that the vast bulk of that biodiversity remains virtually unstudied or even unknown, is to use biogeographic data to make a comprehensive map of regions of endemism in Sulawesi and to protect primary habitat in each region. We present a hypothesis that we call the â€œhybrid biogeographic hypothesisâ€ that synthesizes two previous biogeografic hypotheses, one from empirical biological data and one from geologic data. We present a map of tarsier acoustic group distributions that offers heuristic evidence that the former hypothesis is more comprehensive than either of the latter two. We note that some of these regions have multiple conservation areas, while several others have none at all and can be thought of as â€œhotspots within the hotspotâ€. Evidence indicates that an endemic taxon of tarsier inhabits nearly every known endemic region of Sulawesi and surrounding island chains, although most of these taxa are undescribed. We propose to use tarsiers as flagship species to justify new conservation areas that will preserve primary habitat in those regions that currently lack them. Tarsiers are superior to other potential flagship species because they have the requisite charisma and are distributed throughout Sulawesi in a broad variety of habitats, but they do not eat agricultural products or have other characteristics that might engender local resentment to their conservation. This plan requires naming several new taxa of tarsiers, each of which requires reference material. Existing museum populations are inadequate for these needs and new museum specimens are required. We argue that the most beneficial way for this program to proceed is to trap wild tarsiers and house them in captivity until they expire naturally, at which time they will enter the collections of the Museum Zoologicum Bogoriense. While in captivity these tarsiers will provide enormous opportunities for research, training, education, and conservation. We will encounter local resistance to conserving tarsier populations because of false perceptions among inhabitants that tarsiers eat agricultural products, and this false belief must be corrected through community education. The critical condition of habitat destruction in Sulawesi warrants immediate action.